2013
DOI: 10.2528/pier12110104
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Atmospheric Duct From Radar Sea Clutter Using Artificial Bee Colony Optimization Algorithm

Abstract: Abstract-In this study, the Artificial Bee Colony Optimization (ABCO) algorithm has been proposed to estimate the atmospheric duct in maritime environment. The radar sea clutter power is calculated by the parabolic equation method. In order to validate the accuracy and robustness of ABCO algorithm, the experimental and simulation study are respectively carried out in the current research. In the simulation study, the statistical analysis of the estimation results in term of the mean squared error (MSE), mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Therefore, electromagnetic waves propagating in the atmosphere are affected by atmospheric refraction. Atmospheric refractivity is defined by [15] N = (n − 1) × 10 6 (1)…”
Section: Atmospheric Ductsmentioning
confidence: 99%
“…Therefore, electromagnetic waves propagating in the atmosphere are affected by atmospheric refraction. Atmospheric refractivity is defined by [15] N = (n − 1) × 10 6 (1)…”
Section: Atmospheric Ductsmentioning
confidence: 99%
“…Zhang et al introduced a four-parameter modified refractivity profile model for the evaporation duct estimation with RFC [11]. The artificial bee colony (ABC) algorithm [12, 13] inspired by the intelligent foraging behavior of honey bee swarm is one of the most recently proposed bio-inspired swarm intelligence algorithm, and it is applied to the electromagnetic optimization problem [13] and atmospheric duct estimation [14, 15]. Yang employed the ABC to the atmospheric duct estimation, and the results showed that the performance of ABC is better than particle swarm optimizer according to the comparative analysis results [14].…”
Section: Introductionmentioning
confidence: 99%
“…The artificial bee colony (ABC) algorithm [12, 13] inspired by the intelligent foraging behavior of honey bee swarm is one of the most recently proposed bio-inspired swarm intelligence algorithm, and it is applied to the electromagnetic optimization problem [13] and atmospheric duct estimation [14, 15]. Yang employed the ABC to the atmospheric duct estimation, and the results showed that the performance of ABC is better than particle swarm optimizer according to the comparative analysis results [14]. Yang et al proposed the ABC algorithm combined with opposition-based learning and global best search equation (OGABC) to improve the problems of the slow convergence speed and sinking into local optima appear in the duct estimation problem, and investigation results indicate that the OGABC achieves good performance compared with the ABC and the modified invasive weed optimization [15].…”
Section: Introductionmentioning
confidence: 99%
“…Taking the nonlinear relation between the forward propagation model and atmospheric duct parameters into consideration, the investigation on the optimization models with high performance is one of the most important research topics in the field of inversion of the atmospheric duct from radar sea clutter. For instance, the least square support vector machine, the particle swarm optimization (PSO), the simulated annealing algorithm, and the ABC algorithm have been applied to infer the atmospheric duct using RFC technique [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the ABC algorithm has been applied to the design of antenna and electromagnetic devices [13][14][15]. In addition, the ABC algorithm has been used to infer the atmospheric duct from RFC technique [11], and the comparative study results demonstrate that the performance of ABC is superior to that of the PSO for the inversion of atmospheric duct. However, the ABC also has the drawbacks of easily falling into local optima and slower convergence rate.…”
Section: Introductionmentioning
confidence: 99%